Geometry of the Pamir‐Hindu Kush intermediate‐depth earthquake zone from local seismic data. Issue 4 (8th April 2013) - Sippl, C.; Schurr, B.; Yuan, X.; Mechie, J.; Schneider, F. M.; Gadoev, M.; Orunbaev, S.; Oimahmadov, I.; Haberland, C.; Abdybachaev, U.; Minaev, V.; Negmatullaev, S.; et al.
Abstract : [1] We present new seismicity images based on a two‐year seismic deployment in the Pamir and SW Tien Shan. A total of 9532 earthquakes were detected, located, and rigorously assessed in a multistage automatic procedure utilizing state‐of‐the‐art picking algorithms, waveform cross‐correlation, and multi‐event relocation. The obtained catalog provides new information on crustal seismicity and reveals the geometry and internal structure of the Pamir‐Hindu Kush intermediate‐depth seismic zone with improved detail and resolution. The relocated seismicity clearly defines at least two distinct planes: one beneath the Pamir and the other beneath the Hindu Kush, separated by a gap across which strike and dip directions change abruptly. The Pamir seismic zone forms a thin (approximately 10 km width), curviplanar arc that strikes east‐west and dips south at its eastern end and then progressively turns by 90° to reach a north‐south strike and a due eastward dip at its southwestern termination. Pamir deep seismicity outlines several streaks at depths between 70 and 240 km, with the deepest events occurring at its southwestern end. Intermediate‐depth earthquakes are clearly separated from shallow crustal seismicity, which is confined to the uppermost 20–25 km. The Hindu Kush seismic zone extends from 40 to 250 km depth and generally strikes east‐west, yet bends northeast, toward the Pamir, at its eastern end. It may be divided vertically into upper and lower parts separated by a gap at approximately 150 km depth. In the upper part, events form a plane that is 15–25 km thick in cross section and dips sub‐vertically north to northwest. Seismic activity is more virile in the lower part, where several distinct clusters form a complex pattern of sub‐parallel planes. The observed geometry could be reconciled either with a model of two‐sided subduction of Eurasian and previously underthrusted Indian continental lithosphere or by a purely Eurasian origin of both Pamir and Hindu Kush seismic zones, which necessitates a contortion and oversteepening of the latter. Key points: Automatized seismogram picking and location of 9532 earthquakes Pamir‐Hindu Kush intermediate‐depth seismicity defines two distinct structures Geometry hints at subduction or delamination of lower crustal material